The devil’s in the details: data exchange in transboundary waters - Mukuyu, Patience; Lautze, Jonathan F.; Rieu-Clarke, A.; Saruchera, D.; McCartney, Matthew P. (Informa UK Limited, 2020)
Data exchange in transboundary waters is fundamental to advance cooperative water management. Nonetheless, the degree to which data are shared is not well understood. To gauge this degree, an assessment framework was developed and applied in 25 international river basins. The framework captures the degree to which a set of data parameters is exchanged among countries. A reasonable proportion of surveyed basins exchange some data, but the breadth of such exchange is often limited, and not regular. This paper highlights where data exchange can be improved and provides guidance on how indicators used in global assessment frameworks can motivate this improvement.